Working with children : assessment, representation and intervention - Billington, Tom, 1952- (SAGE, 2006)
Written for professionals working with children and young people who require support, assessment or intervention at home or in school, this interdisciplinary book explores everything from the legislative background and foundations of ideas in the social sciences, to dealing with children's distress, fear or special needs in professional practice. The book is an excellent resource for those who either work with children in Child and Adolescent Mental Health Services settings, social work, youth work, counselling, psychology, general education and special educational needs or who are undertaking.